2017
DOI: 10.1177/0093854817715289
|View full text |Cite
|
Sign up to set email alerts
|

The Risk-Need-Responsivity Model Revisited: Using Biosocial Criminology to Enhance Offender Rehabilitation

Abstract: During the past four decades, researchers and practitioners working in corrections have shifted from a “nothing works” to a “what works” orientation. Emphasizing the importance of adopting evidence-based interventions, Andrews and Bonta have argued that efforts to rehabilitate offenders should adhere to a number of specified principles of effective intervention, three of which—risk, need, and responsivity—are considered the most critical. These principles were derived from Andrews and Bonta’s theory of the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 132 publications
0
15
0
Order By: Relevance
“…Overall, it was concluded that neuropsychologists should play an important role assisting with the prediction and management of criminal behavior in correctional settings. Newsome and Cullen (2017) proposed further theoretical development of the RNR model by integrating biosocial research. Our analyses of promising neuropsychological contributions to RNR support their contention.…”
Section: Conclusion and Further Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it was concluded that neuropsychologists should play an important role assisting with the prediction and management of criminal behavior in correctional settings. Newsome and Cullen (2017) proposed further theoretical development of the RNR model by integrating biosocial research. Our analyses of promising neuropsychological contributions to RNR support their contention.…”
Section: Conclusion and Further Studymentioning
confidence: 99%
“…The link between social-cognitive theories of criminality and biosocial perspectives is an important consideration in forensics (Beaver, Wright, & DeLisi, 2007;Jantz & Morley, 2018). For example, Newsome and Cullen (2017) applied "biosocial criminology" to Andrews and Bonta's risk-need-responsivity (RNR) model, and the RNR model is arguably the most comprehensive and empirically supported theory of the origins, assessment, and treatment of antisocial behavior (Bonta & Andrews, 2017). In response to Newsome and Cullen, we specifically consider the potential for neuropsychological research to advance the RNR model.…”
mentioning
confidence: 99%
“…This means that efforts to reduce recidivism in males may not be effective when applied in a one-size-fits-all manner that does not account for individual differences among offenders, and that more targeted interventions based on individual differences may be necessary to reduce rates of reoffending. The results of this study, and others, suggest that indirect measures of neurological functioning should be incorporated into offender risk assessments, and measures of biomarkers, and the results of biosocial criminological research in general should be disseminated to practitioners and policymakers (Newsome & Cullen, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…Newsome and Cullen (2017) highlight a need to expand the conceptual grounding of the RNR model. To date, there has been no attempt to examine the RNR model and collective efficacy theory simultaneously.…”
Section: The Present Studymentioning
confidence: 99%